ETIO-PATHOGENETIC FORMS OF STOMATOGENIC MAXILLARY SYNUSITIS - Varzhapetіan S.D.; Gulyuk, A.G. (World of Medicine and Biology, 2018)
Comparative analysis of the results of ultrasound examination of maxillary sinuses of patients with various etiopathogenetic forms of stomatogenic maxillary sinusitis. We used digital data which we obtained in studies of the frequency of occurrence of various ultrasound criteria of the maxillary sinus of the 86 patients of etio-pathogenetic groups of stomatogenic maxillary sinusitis for statistical calculations. The maximum variation in the thickness of the Schneider’s membrane in groups of patients with sinusitis of iatrogenic etiology was observed in medicamentous (drug) and infectious-allergic forms: respectively – in groups where, like in control group, prevails infectious component in the etiopathogenesis of the disease. Significantly lower from the above data were indicators for traumatic and mixed forms of iatrogenic sinusitis respectively 26.0 % and 23.7 % (p